NCMP-21. IMMUNE-RELATED ACUTE MOTOR AXONAL NEUROPATHY: A SMALL CASE SERIES AND REVIEW OF THE LITERATURE. (12th November 2021) - Pina, Yolanda; Tran, Nam; Verma, Neha; Vogelbaum, Michael; Forsyth, Peter; Mokhtari, Sepideh; Peguero, Edwin
Abstract: BACKGROUND: Immunotherapy revolutionized cancer treatment in the past decade, with a significant increased survival in patients with solid tumors. However, immune checkpoint inhibitors (ICIs) have been associated with a growing number of neurotoxicities, some of which can be fatal if not recognized and treated promptly. Some of these neurotoxicities include very uncommon syndromes like Acute Motor Axonal Neuropathy (AMAN). Herein we present four oncological cases of patients who underwent immunotherapy and developed AMAN. METHODS: Four patients were diagnosed with immune-related AMAN between 2017 and 2000 at H. Lee Moffitt Cancer Center. Patients were treated with standard of care. RESULTS: We describe four oncological patients who developed a motor axonal neuropathy (i.e., AMAN) confirmed on nerve conduction studies following 2 cycles of immunotherapy, including a 28 year old woman with melanoma brain metastasis and a 50 year old woman with renal cell carcinoma both treated with ipilimumab and nivolumab, a 32 year old man with Hodgkin lymphoma who was treated with nivolumab and brentuximab, and a 77 year old woman with renal urothelial cancer who was treated with pembrolizumab and cabozantinib. All four patients were promptly recognized as having immune-related neurotoxicity (irNs), were promptly treated (i.e., high dose steroids +/- IVIG +/- other immunomodulators), and significantly improved and have remained stable. CONCLUSION: This is the first case series of patients with AMAN following two cycles of immunotherapy, who were successfully treated. It is crucial to develop a better understanding of irNs, including those rare conditions that are difficult to diagnose and treat, as the utilization of these immunomodulating therapies continues to expand to include other solid malignancies. Neurologists should be involved early on in any case of suspected irN to assist in the management of these complicated patients and a swift work up should be initiated for timely diagnosis and treatment.